Study on Particulate Matter (PM) Emissions of Diesel Engine Using Palm Oil Methyl Ester - Nur Fauziah, Jaharudin; Abdul Adam, Abdullah; Ahmad Fitri, Yusop; R., Mamat; Nur Atiqah, Ramlan; Mohd Herzwan, Hamzah (Trans Tech Publications Inc., 2014)
One of the major pollutants emitted by diesel engine is particulate matter (PM). The main concerns about PM are their adverse effects in the urban area. Therefore researchers are now constantly working on alternative fuels which are clean and efficient in combustion. One of the most promising alternatives fuel is vegetable oils and their derivatives. Based on this study, the characteristics of indirect injection diesel engine in term of the PM have been investigated experimentally. The experiments were conducted experimentally using four cylinder diesel engine. This paper presents an experimental study of PM using mineral diesel and palm-diesel (B100) as a fuel. The result shows highest percentage count for both mineral-diesel and palm-diesel at PM diameter range of 121-160 nm. In addition, the result also indicates that at 2500 rpm the PM for palm-diesel is lower than mineral-diesel for all size range. Thus, at 2500 rpm, it is the optimum speed in order to have a minimum PM for palm-diesel.